2011
DOI: 10.1177/1744629511403649
|View full text |Cite
|
Sign up to set email alerts
|

Preventing abuse in accommodation services: From procedural response to protective cultures

Abstract: This article reviews current approaches of disability accommodation services to addressing the abuse and neglect of people with intellectual disability who live in them. We review international literature and provide practice examples from accommodation services for people with intellectual disability in Australia to develop a framework of current research, policy and practice in this area. The results of this review show that dominant policy and practice approaches do not give adequate consideration to the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
40
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 30 publications
3
40
0
Order By: Relevance
“…Our search found one result focusing on responses to violence in institutions, but it failed to meet the inclusion criteria (Robinson & Chenoweth, 2011). A UNICEF report on violence against disabled children confirmed that violence in institutions is particularly widespread, which may imply that deinstitutionalization would be an appropriate violence prevention strategy, but none of the studies focused on this area (UNICEF, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…Our search found one result focusing on responses to violence in institutions, but it failed to meet the inclusion criteria (Robinson & Chenoweth, 2011). A UNICEF report on violence against disabled children confirmed that violence in institutions is particularly widespread, which may imply that deinstitutionalization would be an appropriate violence prevention strategy, but none of the studies focused on this area (UNICEF, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…As she moved into the role as advocate she was at times highly critical of the group home care, making direct contact with staff when she thought Heather's personal care was being compromised. Although having an advocate and someone to monitor wellbeing reduces risk of harm (Robinson & Chenoweth, 2011), it also has the potential to create tensions between services. Risks such as these are inevitable if people with severe intellectual disability, such as Heather, are going to be socially included and have relationships with community members beyond the service system.…”
Section: Discussionmentioning
confidence: 99%
“…This centres on the importance of having active, engaged supporters in your life, and the value of community and unpaid relationships. There are clear implications for policy and practice here Á supportive relationships outside of disability systems are protective (Coulson Barr 2012;MacArthur 2003;Mansell 2006;Robinson and Chenoweth 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Models of abuse prevention arising from public health which focus at primary, secondary and tertiary levels recognize the need for a multi-layered, multi-strategy approach to a complex problem, advocating community level responses, responses geared to specific groups at higher risk of harm, and resources and attention to assistance for people who have experienced harm for their support and recovery (see for example, Fitzsimons 2009). Other approaches emphasize the relational nature of protection Á the importance of having engaged, supportive people in your life and the value of unpaid relationships and meaningful community engagement (Coulson Barr 2012;MacArthur 2003;Mansell 2006;Robinson and Chenoweth 2011). …”
mentioning
confidence: 99%